Changes in gait parameters and pelvic movement during gait under the influence of light loads carried symmetrically or asymmetrically - preliminary research - Katarzyna Wódka; Sylwia Łachut; Agnieszka Jankowicz-Szymańska (University of Applied Sciences in Tarnow, Poland, 2023)
Introduction: Walking is one of the basic human activities. Taking care of the correct gait pattern is important for maintaining proper body posture and preventing dysfunctions of the musculoskeletal system. Since walking often involves carrying a load, the study aimed to evaluate changes in gait parameters and pelvic movement during gait under the influence of light loads carried symmetrically or asymmetrically in a bag or backpack. Material and methods: The group of 11 women and 15 men aged between 19 and 25 were examined. The BTS G-Sensor device was used. The basic gait parameters were examined, as well as the symmetry coefficient of pelvic motion and the range of pelvic motion in each of the three planes. The test involving walking 30 meters was repeated four times: while walking without a load, with an additional load worn in a backpack on both shoulders, in a bag on the right shoulder, or in a bag worn diagonally on the left shoulder. Each time the load was equal to 10% of the participantʼs body weight. Results: Walking speed, stride length to body height ratio, gait symmetry coefficient, and left and right foot propulsive speed did not change significantly during walking while carrying a load of 10% of body weight, regardless of the method of carrying a bag or backpack. Conclusions: Although carrying a light bag or backpack does not change the basic gait parameters, even such a small load reduces the symmetry of pelvic movement and the range of pelvic motion in the frontal and transverse planes during walking.